Barry's introduction to construction of buildings - Emmitt, Stephen; Gorse, Christopher A. (Chichester, U.K. : Wiley-Blackwell Pub., 2010)
'This new edition of Barry's Introduction to Construction of Buildings adds considerable new material but remains based on the original concept of explaining construction technology through key functional/performance requirements for the main elements common to all buildings. Of particular note in this new edition are a fully integrated approach to environmental issues and construction sustainability. The rest of the material has been updated as required, with particular attention paid to the illustrations. With over 150 new photographs and many revised figures, plus a supporting website at www.wiley.com/go/barrysintroduction, students learning the fundamentals of building and construction on undergraduate and other NQF level 5-6 courses will find this the ideal introduction to the subject.'--Publisher's description.
Includes bibliographical references and index.
Includes web resources.
Keywords: Building